PERLINDUNGAN KREDITOR ATAS KEWENANGAN MUTLAK OTORITAS JASA KEUANGAN TERHADAP PERMOHONAN PERNYATAAN PAILIT PERUSAHAAN PERBANKAN - Khardin Khardin; Anwar Borahima; Winner Sitorus (UNES Law Review, 2023)
The revocation of a bank's business license by OJK does not eliminate its status as a bank. Therefore, there is no opportunity for Creditors to apply bankruptcy statements for a bank because this authority absolutely rests with the OJK. Legal protection for Creditors can be pursued by the OJK by immediately resolving the bank through bankruptcy proceedings if the liquidation process is problematic, or the liquidation team formed by LPS gives advice to the OJK to make bankruptcy efforts if liquidation process it is found that the amount of debt is higher than the bank's assets, or the Creditor may take other legal remedies by filing a civil lawsuit on the basis of default. This research is a normative legal research. The type of it uses is a statute and conceptual approaches. The types and sources of legal materials used are primary legal materials and secondary legal materials related to the object of research. Literature research used to collect legal materials. This research uses a qualitative analysis which is prescriptive.